Improving private security–youth relations in quasi-public spaces: control, care, cooperation - Saarikkomäki, Elsa (International journal of comparative and applied criminal justice, 2022)
The global growth of the private security sector is connected to the increasing number of quasi-public spaces policed as private ones but used as public ones. The intensive policing of young people in shopping centres has, however, led to problematic private security–youth relations. This article focuses on a new method in which youth workers train security guards to improve these relations in shopping centres in Finland. The study uses qualitative content analysis to explore unique data – security guards’ daily reports. The encounters displayed control, care and cooperation: security guards controlled the youths’ activities but also talked with them and helped them. The study argues that the role of security guards is even more plural and blurred than previously understood, including a “social” orientation, and cooperation with public, private and third sector agents. Finally, the study highlights the importance of developing procedural justice, both in theory and in practice.